2015
DOI: 10.14202/vetworld.2015.1063-1067
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological studies on forestomach disorders in cattle and buffaloes

Abstract: Aim:To study epidemiology of forestomach (reticuloruminal, omasal, and abomasal) disorders in cattle and buffaloes.Materials and Methods:The 106 buffaloes and 32 cattle referred for treatment to the university large animals teaching hospital with the complaint of gastrointestinal diseases constituted the study material. The cases were diagnosed based on history, clinical examination, hematology, biochemistry, radiography, peritoneal fluid analysis and ultrasonography, rumenotomy, and postmortem. A questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 6 publications
(7 reference statements)
5
8
2
2
Order By: Relevance
“…In the present study, incidence of rumen impaction cases is more in first lactation and least in fifth lactation. This finding is in contravention to those by Sharma et al (2015) who reported that incidence of impaction increased with lactation number. In present investigation, no significant changes were observed in haemoglobin, packed cell volume and total erythrocyte count.…”
Section: Resultscontrasting
confidence: 73%
“…In the present study, incidence of rumen impaction cases is more in first lactation and least in fifth lactation. This finding is in contravention to those by Sharma et al (2015) who reported that incidence of impaction increased with lactation number. In present investigation, no significant changes were observed in haemoglobin, packed cell volume and total erythrocyte count.…”
Section: Resultscontrasting
confidence: 73%
“…Hussain et al (2018) also recorded prevalence of foreign Body Syndrome in cattle ranging from 23% to 87%. Sharma et al (2015) found that of all the fore stomach disorders in cattle, 41.01% were of FBS including diaphragmatic hernia. He also recorded that the incidence in females (94.73%) was more as compared to males (5.27%) which correlates with the findings of the present study.…”
Section: Incidencementioning
confidence: 99%
“…The disease has economically a great impact as it causes severe reduction of milk and death of animals. The magnitude of loss to dairy industry can be assessed from the fact that this complex has been responsible for more than 15 % of all the natural deaths in dairy and beef animals (Sharma et al, 2015). In India, it has a high prevalence ranging from 23% to 87% (Hussain et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A síndrome do corpo estranho está amplamente distribuída em todo o mundo (ROTH; KING, 1991;CRAMERS et al, 2005;SHARMA;DHALIWAL;RANDHAWA, 2015). No Brasil, não há estimativas da ocorrência.…”
Section: Epidemiologiaunclassified